PERBEDAAN TINGKAT PENGETAHUAN MASYARAKAT PEDESAAN DAN PERKOTAAN TENTANG 5M SEBAGAI PENCEGAHAN PENULARAN CORONAVIRUS DISEASE-19 - yusni mariance benu; Erna Febriyanti; Sebastianus Kurniadi Tahu (CHMK NURSING SCIENTIFIC JOURNAL, 2022)
Background: Covid-19 is a dangerous infectious disease caused by SARS Coronavirus-2. Until now, there has been no treatment that is considered effective to treat Covid-19 patients, so it is very important to prevent Covid-19, including 5M. This is inseparable from the 5M knowledge that is evenly distributed in the community. Although the majority of urban communities apply 5M, the minority does not, while rural communities tend to apply 5M when there are COVID-19 task force officers. The results of interviews with 5 Kayu Putih communities showed that on average the people answered that 5M was important to prevent covid-19.Objective: This study aims to determine the difference in the level of knowledge about the 5M prevention of covid-19 in rural and urban communities. Method: This research is a quantitative research with a comparative design. The sampling technique in this study used a total sampling of 55 people for rural communities and quota sampling for urban communities, amounting to 51 people. This research was conducted in RT 002 RW 001, Manufui Village, Santian District, South Central Timor Regency and RT 02 RW 01, Kayu Putih Village, Oebobo Subdistrict, Kupang City using a questionnaire describing the 5M knowledge of Covid-19 prevention with the Mann-Whitney statistical test. Result: There is a difference in the level of 5M knowledge in rural and urban communities with a mean rank value of 33.60 in rural and 74.96 in urban areas, while the p value = 0.000 (<0.05).Conclusion: There are differences in the level of knowledge of the 5M Covid-19 prevention in rural and urban communities. Keywords: 5M prevention of Covid-19, Knowledge, Differences, Rural, Urban